The appreciation for international standards on quality management: Lessons from researchers - Rogala, Piotr; Arsić, Sanela; Brzozowski, Tomasz (Międzynarodowe standardy zarządzania jakością w ocenie badaczy, 2019)
The purpose of the paper is to determine scientists’ opinion on the ISO 9000 series of international standards on quality management. Two research methods were applied: a literature review and a survey. It was found that the ISO 9000 series standards are acceptable and appreciated by scientists. The most significant benefits resulting from their existence are: promoting quality management in practice, helping understand the essence of quality management and allowing implementing successful solutions in the area of quality management. The main contributions of the study are twofold. Firstly, the research made a holistic evaluation of the international standards on quality management. Secondly, the significance of the standards in the area of the quality management movement was evaluated. There were two limitations connected to conducted research; the first may derive from the fact that Polish dominated in the study sample and the second could derive from the fact that it focused only on the opinions of scientists dealing with quality management
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 209-222
Keywords: quality management; ISO 9000; ISO 9001; benefits; zarządzanie jakością; korzyści